A description of antipsychotic prescribing patterns based on race in the inpatient behavioral health setting. (June 2021) - Maestri, Thomas; Anderson, David; Calderon-Abbo, Jose; Waguespack, Taylor; Echeverri, Margarita
Background and aims: A growing body of research shows that race contributes to disparities in mental health services utilization and influences the clinical diagnostic process. To our knowledge, no studies on current practice in the Unites States have documented whether these disparities impact the prescription of antipsychotic medications across individual patients based on race. Consequently, this study aims to describe the prescribing patterns of antipsychotic medications in the inpatient setting based on patients' race, and to explore appropriateness of therapy based on Food and Drug Administration labeling and avoidance of inappropriate polypharmacy. Methods: Single-centered, retrospective, chart review of 398 psychiatric patients in the inpatient setting and who had a psychiatric diagnosis that warranted a prescription for an antipsychotic medication at the time of discharge. Frequencies were computed to describe differences in demographic variables (race, health insurance type, age, and gender), medical conditions (diagnosis, commodities, hospitalization status, antipsychotic medications, etc.), and screening tests (lipid panel, hemoglobin, urine and illicit drug use). Logistic regression, analysis of variance, and hypothesis tests were used to analyze the data. Results: Significant differences were not found in total chlorpromazine equivalent dose equivalencies by race or insurance. However, patients of involuntary admission status, past medication trials, a diagnosis of schizophrenia or bipolar disorder, and who lacked family support had higher total daily doses of antipsychotics upon discharge. Inappropriate therapy was significantly related to differences in increasing age and a diagnosis of insomnia. Conclusion: This single-centered study described patterns of antipsychotic prescribing based on race in an inpatient psychiatry facility. Future studies, using larger and more diverse sample populations, are recommended to elucidate the role that patients' race, admission status, and family support play in the dose and appropriateness of antipsychotics prescribed for mental health care.